Innovative Learning: Gender Perception of e-Module Linear Equations in Mathematics and Physics - Dwi Agus Kurniawan; Astalini Astalini; Darmaji; Tanti; Shella Maryani (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2022)
This research was conducted to answer students' perceptions based on gender towards the e-Module Mathe-matics Physics I on linear equations. This methodology uses quantitative research which is analyzed using statistical and inferential analysis techniques with a sample of 120 students. After testing, the results sho-wed that the perceptions of male students and female students' perceptions were concluded that the average value of female students' perceptions had differences. From the difference in the average value of student perceptions based on gender in the research sample, it shows that the perception of students with male gen-der is higher than the average value of female gender perception because male students tend to have critical thinking skills towards material. related to mathematics compared to female students.